An Analysis of Gamification in Boosting Training Effectiveness: The Mediating Role of Engagement - Vitriawaty; Paula Lukita; Edwin Ibnu Margani; Tengku Mohd. Khairal Abdullah (International Journal of Business Studies, 2026)
This study explores how gamification influences the effectiveness of training in a corporate middle management program. Based on Social Cognitive Theory (SCT), it aims to fill the mechanistic gap by proposing and empirically testing a mediation model to understand how gamification works, focusing on whether its impact is mediated through participant engagement. The study used a quantitative, explanatory survey design. Data was gathered from 214 participants in the "Leading and Empowering Your Team" module, a key part of the Astra Middle Management Program (AMMP). The proposed mediation model was evaluated using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The model exhibited excellent predictive accuracy, accounting for 68.6% of the variance in Training Effectiveness and 56.4% in Engagement. Path analysis verified that all hypothesized relationships were strong and statistically significant. Gamification had a significant impact on training effectiveness ( β = 0.599, p < 0.001). Additionally, a notable indirect effect was observed (β = 0.209, p = 0.006), indicating that Engagement mediates this relationship (β for GAM -> ENG = 0.751; β for ENG -> TEF = 0.278). This study offers solid empirical evidence for the two main ways gamification functions. It shows that gamification is not merely a gimmick for "fun" (engagement), but also serves as a strong cognitive instrument that enhances learning directly. The research highlights Engagement as a crucial mechanism, providing T&D practitioners with a clearer understanding of how their gamified strategies accomplish their goals.